The mycorrhizal type governs root exudation and nitrogen uptake of temperate tree species. (8th November 2017) - Liese, Rebecca; Lübbe, Torben; Albers, Nora W; Meier, Ina C
Abstract: Even though the two dominant mycorrhizal associations of temperate tree species differentially couple carbon (C) and nitrogen (N) cycles in temperate forests, systematic differences between the biogeochemical cycles of arbuscular mycorrhizal (AM) and ectomycorrhizal (ECM) tree species remain poorly described. A classification according to the mycorrhizal type offers the chance, though, to develop a global frame concept for the prediction of temperate ecosystem responses to environmental change. Focusing on the influence of mycorrhizal types on two key plant processes of biogeochemical cycling (root exudation and N acquisition), we investigated four temperate deciduous tree species per mycorrhizal type in a drought experiment in large mesocosms. We hypothesized that (H1) C loss by root exudation is higher in ECM than in AM trees, (H2) drought leads to higher reductions in root exudation of drought-sensitive ECM trees and (H3) inorganic N uptake is higher in AM than in ECM trees. In contradiction to H2, we found no systematic difference in root exudation between the mycorrhizal types at ample soil moisture, but almost twofold higher exudation in ECM trees when exposed to soil drought. In addition, photosynthetic C cost of root exudation strongly increased by ~10-fold in drought-treated ECM trees, while it only doubled in AM trees, which confirms H1. With respect to H3, we corroborated that AM trees had higher absolute and relative inorganic N acquisition rates than ECM trees, while the organic N uptake did not differ between mycorrhizal types. We conclude that ECM trees are less efficient in inorganic N uptake than AM trees, but ECM trees increase root C release as an adaptive response to dry soil to maintain hydraulic conductivity and/or nutrient availability. These systematic differences in key biogeochemical processes support hints on the key role of the mycorrhizal types in coupling C and N cycles in temperate forests.